Bile acid-induced arrhythmia is mediated by muscarinic M2 receptors in neonatal rat cardiomyocytes. - Siti H Sheikh Abdul Kadir (Public Library of Science (PLoS), 2010)
Background Intrahepatic cholestasis of pregnancy (ICP) is a common disease affecting up to 5% of pregnancies and which can cause fetal arrhythmia and sudden intrauterine death. We previously demonstrated that bile acid taurocholate (TC), which is raised in the bloodstream of ICP, can acutely alter the rate and rhythm of contraction and induce abnormal calcium destabilization in cultured neonatal rat cardiomyocytes (NRCM). Apart from their hepatic functions bile acids are ubiquitous signalling molecules with diverse systemic effects mediated by either the nuclear receptor FXR or by a recently discovered G-protein coupled receptor TGR5. We aim to investigate the mechanism of bile-acid induced arrhythmogenic effects in an in-vitro model of the fetal heart. Methods and results Levels of bile acid transporters and nuclear receptor FXR were studied by quantitative real time PCR, western blot and immunostaining, which showed low levels of expression. We did not observe functional involvement of the canonical receptors FXR and TGR5. Instead, we found that TC binds to the muscarinic M(2) receptor in NRCM and serves as a partial agonist of this receptor in terms of inhibitory effect on intracellular cAMP and negative chronotropic response. Pharmacological inhibition and siRNA-knockdown of the M(2) receptor completely abolished the negative effect of TC on contraction, calcium transient amplitude and synchronisation in NRCM clusters. Conclusion We conclude that in NRCM the TC-induced arrhythmia is mediated by the partial agonism at the M(2) receptor. This mechanism might serve as a promising new therapeutic target for fetal arrhythmia.